DETERMINAN STRUKTUR MODAL SERTA DAMPAKNYA PADA NILAI PERUSAHAAN MAKANAN DAN MINUMAN - Amri Amrulloh; Ambar Widati (Pusat Riset dan Inovasi Nasional, 2022)
The company will continue to improve its fundamentals to increase investor interest in investing. With a company that is engaged in providing basic human needs, namely food and beverages, investors are considered to be interested in the market that continues to grow in the industry. This research aims to examine the direct and indirect effect on firm size, profitability on firm value through mediation of capital structure in manufacturing food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2016–2020 period using purposive sampling method. There are 13 manufacturing companieson food and beverage industry selected as samples. The analytical method used is path analysis using the SmartPLS version 3.0 software program. From the results of this research it can be concluded that firm size has a significant effect on capital structure, profitability has no significant effect on capital structure, firm size has no significant effect on firm value, profitability has a significant effect on firm value, capital structure has a significant effect on firm value, firm size has an effect significant effect on firm value through capital structure mediation, profitability has no significant effect on firm value through capital structure mediation. However, companies will continue to compete to increase the firm value to increase investor interest in investing by paying attention to the variables contained in the financial statements.